Synthesis of Pyrroles and Thiazolanes Promoted by N-Methylimidazole in Water - Rostami-Charati, Faramarz (Synlett, 2014)
A convenient and efficient approach to the synthesis of substituted pyrroles is reported based on three-component reaction of primary amines and alkyl propiolates in the presence of N-methylimidazole in water. A water-accelerated synthesis of thiazolane derivatives has also been established by employing the three-component reaction of primary amines, alkyl propiolates, and isothiocyanates in the presence of N-methylimidazole.
Keywords: N-methylimidazole; pyrrole; thiazolane; three-component reaction